Assessment of cassava supply response in Nigeria using vector error correction model (VECM) (2016)
The response of agricultural commodities to changes in price is an important factor in the success of any reform programme in agricultural sector of Nigeria. The producers of traditional agricultural commodities, such as cassava, face the world market directly. Consequently, the producer price of cassava has become unstable, which is a disincentive for both its production and trade. This study investigated cassava supply response to changes in price. Data collected from FAOSTAT from 1966 to 2010 were analysed using Vector Error Correction Model (VECM) approach. The results of the VECM for the estimation of short run adjustment of the variables toward their long run relationship showed a linear deterministic trend in the data and that Area cultivated and own prices jointly explained 74% and 63% of the variation in the Nigeria cassava output in the short run and long-run respectively. Cassava prices (P< 0.001) and land cultivated (P<0.1) had positive influence on cassava supply in the short-run. The short-run price elasticity was 0.38 indicating that price policies were effective in the short-run promotion of cassava production in Nigeria. However, in the long-run elasticity cassava was not responsive to price incentives significantly. This suggests that price policies are not effective in the long-run promotion of cassava production in the country owing to instability in governance and government policies.